Há uma luta de classes nos livros: política cultural para a democratização do livro e leitura no Brasil no contexto neoliberal - MARTINS, Carlos Wellington Soares (2019)
Public policies of culture, or cultural policies, have advanced in their formulation and implementation and have gained relevance as a category of analysis and in the way it occupies space in the governmental agenda, be it at the federal, state and municipal levels. The democratization of books and reading are guided by a cultural policy developed by Minc and MEC in an interministerial action, but with predominance of actions by the culture folder. Under the guidance of Marxist theory, based on the social, political, cultural and economic conjuncture, the predominance of the categories: Ideology, Cultural Politics and Democratization of book and reading and Class struggle stands out in the analysis. The thesis presented has as its object the structural and conjunctural determinants, as well as the political-ideological principles that demarcated the conception of the policy of democratization of books and reading, having as reference the Plano Nacional do Livro e Leitura (PNLL), launched in 2006 , under the government of the then president Luís Inácio Lula da Silva, with the main objective of ensuring and democratizing the access to reading and the book to the whole Brazilian society. It aims to analyze the structural and conjunctural determinants that define the political-ideological aspects present in the conception and elaboration of the national public reading policy through PNLL. It was sought to unveil the correlation of forces that influenced the democratization of the book and of reading through insertion in the governmental agenda as national politics. The thesis defended in this analysis is that the democratization of books and reading in Brazil has its historical trajectory markedly by the traditions: authoritarianism, discontinuities, late character and institutional fragility, easily perceptible in the cultural policies of the book and reading undertaken, which hinders the possibility of building a reading society, but also try to undertake "social inclusion" through access to cultural goods that, in line with the neoliberal ideology, characterize the subjects more as consumers than necessarily able to exercise their full citizenship